2013
DOI: 10.1111/ans.12388
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of the American College of Surgeons Oncology Group Z0011 Trial to breast cancer in the Australian setting

Abstract: Background: Conventional wisdom suggests that a patient with a positive sentinel node requires a completion axillary clearance to obtain full staging and durable regional control. However, this dictum has been challenged by the recent American College of Surgeons Oncology Group Z0011 Trial demonstrating that women with node-positive breast cancer who underwent sentinel node biopsy only, and were treated with breast conserving surgery and radiation, had equivalent locoregional recurrence and survival rates to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 22 publications
2
12
0
Order By: Relevance
“…The Z0011 study is relevant and applicable to many breast cancer patients and when applying the Z0011 criteria to our breast cancer patients, we found that there were 11.8% who fulfilled all the Z0011 criteria. This is comparable to previous studies that showed that it would apply to 9.6% of breast cancer patients, and to about 22% of node positive breast cancer patients in the Australian setting …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The Z0011 study is relevant and applicable to many breast cancer patients and when applying the Z0011 criteria to our breast cancer patients, we found that there were 11.8% who fulfilled all the Z0011 criteria. This is comparable to previous studies that showed that it would apply to 9.6% of breast cancer patients, and to about 22% of node positive breast cancer patients in the Australian setting …”
Section: Discussionsupporting
confidence: 89%
“…This is comparable to previous studies that showed that it would apply to 9.6% of breast cancer patients, and to about 22% of node positive breast cancer patients in the Australian setting. 12 Shortly following the publication of the Z0011 trial, it was described as a practice changing trial. 13 In the years that followed, there have been studies including our current study, affirming this statement.…”
Section: Discussionmentioning
confidence: 99%
“…The application of Z0011 to a European population led to the omission of cALND in less than 10% of all SLNBs and it was therefore concluded that the perception that Z0011 was a “practice changing” trial was unjustified . An Australian study reported that the Z0011 trial is relevant to 9.3% of all breast cancer patients and 21.5% of node‐positive breast cancer patients . We found that 50% of patients with T1 or two tumors and positive SNs met the Z0011 inclusion criteria and that coinciding with the publication of this trial, and there has been a significant reduction in the rate of cALND for these patients (p < 0.001).…”
Section: Discussionmentioning
confidence: 80%
“…Second, depending on the region or treatment facility, the number of patients who may avoid ALND by meeting the Z11 criteria vary significantly. Whereas studies suggest that up to 70%–75% of node-positive patients are applicable to Z11 [7,11,12], other studies have suggested that the applicable proportion is in the range of 10%–20% [15,16]. Therefore, different patient populations surrounding the treating facility may influence the stage of breast cancer and subsequently the applicability of Z11 in various regions.…”
Section: Discussionmentioning
confidence: 99%